The Role of Parents in Their Children's Education - Okello, Millicent (African Journal of Education and Practice, 2023)
Purpose: The purpose of this study is to investigate the role of parents in their children's education. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the role of parents in their children's education. Preliminary empirical review revealed that education in the premises of a family life, has a double meaning: it must be seen through the perspective of its contribution to the overall child raising up and education, which is crucial to his/her proper formation of children's personality and further on, his/her preparation for leading an independent life. Unique Contribution to Theory, Practice and Policy: The Expectancy Value theory and the Ecological Systems theory may be used to anchor future studies on the role of parents in their children's education. The focus must be put on the family as whole, and the role of children which must be based on their approach and contribution concerning family problems, which should be dealt with, and finally solved by them. Offering education support to children from their parents, concerning issues such as homework, would help